Checklist, Bibliography and Quantitative Data of the Arthropods of Hispaniola - Perez-Gelabert, Daniel E. (Zootaxa, 2020)
An updated and extensively revised checklist of the arthropods of Hispaniola (Dominican Republic and Haiti) is presented 11 years after the publication of the original in 2008. It integrates and quantifies all the terrestrial and surrounding marine arthropod species (plus those of Tardigrada and Onychophora), reported in the zoological literature for Hispaniola through the middle of 2019.        A total of 9,920 valid species (8,202 extant and 1,718 fossil) are listed, which represents an increase of 1,683 species (1,369 extant and 314 fossil) from the original list. The largest component is Insecta (6,784 extant and 1,136 fossil), including 2,206 extant species of Coleoptera, 1,042 species of Hemiptera, 929 species of Diptera, 913 species of Lepidoptera and 774 species of Hymenoptera.        Emphasis is on reviewing and updating the original list, including all newly recorded taxa and all pertinent taxonomic changes proposed since then. Important corrections have been made, and explanatory notes have been added. For example, multiple authors have confused the Lesser Antillean island of Dominica with the Dominican Republic. This error is much more common in the literature than was initially recognized. Erroneous records attributing species from one island to the other have been identified and corrected. The original spelling of the cricket species Scapsipedus bastardoi Otte & Perez-Gelabert, 2009, dedicated to Dominican biologist Ruth H. Bastardo, is corrected to Scapsipedus bastardoae nom. emend.        High species endemism is typical of the biota of Caribbean islands. In this checklist, a total of 3,161 arthropod species (38.6%) are considered endemic or unique to Hispaniola. Among the speciose groups with higher levels of endemism are the Diplopoda (91.6%), Orthoptera (90.1%), Trichoptera (82.6%), Coleoptera (49.3%) and Araneae (47.5%). Also, a total of 201 arthropod species (174 insects + 27 non-insects) are identified as introduced to the island.        The accompanying bibliography complements the taxonomic information and includes over 5,000 titles.